The Golden Leaf : How Tobacco Shaped Cuba and the Atlantic World - Cosner, Charlotte, 1969- (Book collections on Project MUSE., 2014)
""Tobacco is one of Cuba's best known commodities, yet its history has been clouded in myth and misconception. This work addresses the ways in which tobacco shaped Cuba and the Atlantic world in terms of culture, society, governmental control, and economics"--Provided by publisher"--